Immunostimulatory activity and structure-activity relationship of epimedin B from Epimedium brevicornu Maxim. - Gao, Yuan; Shi, Wei; Tu, Can; Li, Peng; Zhao, Guanyu; Xiao, Xiaohe; Wang, Jiabo; Bai, Zhaofang (Frontiers in Pharmacology, 2022)
Epimedii Folium (EF), a herbal and dietary supplement, is famous for treating bone fractures, joint diseases, and several chronic illnesses. However, some studies indicated that EF could induce idiosyncratic drug-induced liver injury (IDILI) in the clinic. The NLRP3 inflammasome plays a crucial role in the pathogenesis of various human diseases, including IDILI. In the present study, we showed that epimedin B, a major unhydrolyzed flavonoid glycoside of EF, could specifically facilitate nigericin- or ATP-induced NLRP3 inflammasome activation under synergistic induction of mitochondrial reactive oxygen species. Moreover, epimedin B resulted in activation of Caspase-1 and IL-1β secretion in a lipopolysaccharide (LPS)-mediated susceptibility mouse model. MCC950 pretreatment completely abrogated activation of the NLRP3 inflammasome and prevented liver injury. Importantly, several studies have confirmed that a hydrolyzed flavonoid of EF could enhance activation of the NLRP3 inflammasome and may be involved in the pathogenesis of EF-IDILI. No reports are available on whether the structure-activity relationship associated with the immunostimulatory activity in EF contributes to the pathogenesis of EF-IDILI. These findings have changed our conventional understanding about the more glycogen, the more immunostimulatory activity.